A COMPARATIVE STUDY OF ACADEMIC ACHIEVEMENT AND SATISFACTION IN SOCIAL STUDIES OF GRADE 9 STUDENTS UNDER GAME-BASED AND TEACHER-CENTERED LEARNING METHODS AT SATRIWITTHAYA 2 SCHOOL, BANGKOK Thailand - BANPASAN, BENJAPORN; KARNJANAPUN, SUPIT (Scholar: Human Sciences, 2022)
The purpose of this study was to determine academic achievement and satisfaction between Grade 9 students’ under Game-based learning and Teacher-centered learning methods at Satriwitthaya 2 School, Bangkok. The participants of this study were 60 students from Grade 9 who were studying with game-based and teacher-centered learning methods at Satriwitthaya 2 School, Bangkok. This study was a comparative study research design. In addition, a questionnaire from developing teaching games with computer system for conversion among based on a computer mathematics course at the vocational certificated students. This study analyzed descriptive statistics (means and standard deviations), comparative analysis independent samples t-test (2-tailed). This study found that Grade 9 students’ academic achievement taught by game-based learning method were higher than Grade 9 students’ academic achievement taught by teacher-centered learning method. Furthermore, there was significant difference between Grade 9 students’ academic achievement taught by game-based learning method and those taught by teacher-centered learning method. The satisfaction for the game-based learning was 3.95 and for the teacher-centered learning method was 3.65 which interpreted high.